1987
DOI: 10.1530/acta.0.1150075
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ovarian follicular development as a consequence of low body condition in ewes

Abstract: The effect of body condition on ovarian follicular development was investigated in Scottish Blackface ewes in high and low body condition. Follicles were dissected from ovaries on days 11 and 12 of the luteal phase and 24 h after prostaglandin-induced luteal regression. Ewes in low body condition had a lower ovulation rate (low: 0.9; high: 1.8 P < 0.05) and lower mean plasma levels of FSH during both the luteal (low: 54; high: 72 \g=m\g/l ) and follicular (low: 34; high: 43 \g=m\g/l)phases of the cycle. Low bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Adult ewes maintained on low planes of nutrition exhibited reduced ovulation rates (Haresign, 19811, a response attributed to reduced ovarian follicular development (McNeilly et al, 1987) rather than to an alteration of the preovulatory surge of LH. Effects on follicular development could result from disruption of pulsatile LH release.…”
Section: Estrous Cyclementioning
confidence: 99%
“…Adult ewes maintained on low planes of nutrition exhibited reduced ovulation rates (Haresign, 19811, a response attributed to reduced ovarian follicular development (McNeilly et al, 1987) rather than to an alteration of the preovulatory surge of LH. Effects on follicular development could result from disruption of pulsatile LH release.…”
Section: Estrous Cyclementioning
confidence: 99%
“…Previous studies have shown that in follicles >2.5 mm in diameter, the size beyond which follicles are gonadotrophin dependent in sheep (McNeilly et al . 1986, 1987, McNeilly & Fraser 1987), FF levels of E 2 directly reflect the state of health or atresia of follicles (Carson et al . 1981).…”
Section: Introductionmentioning
confidence: 99%
“…1981). High levels of E 2 reflect healthy preovulatory follicles expressing high levels of LH receptors in both GCs and TCs (Webb & England 1982), and this is correlated with high output of E 2 when the individual follicles are incubated in vitro (Webb & England 1982, McNeilly & Fraser 1987, McNeilly et al . 1987).…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of higher levels of body condition have been shown to be expressed, at least in part, through an increased population of large, potentially ovulatory, ovarian follicles around the time of mating (McNeilly et al 1987), increased levels of food intake before mating do not result in any difference in numbers of large follicles (Rhind & McNeilly 1998). Thus, the differences in ovulation rate associated with the level of food intake must be a function of changes in ovarian activity and in the final processes of oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%